Respostas

2014-04-15T11:38:08-03:00
a) + 25 - (- 4) . (- 5) - 4 - 1 =

25 - 20 - 4 - 1 =
5 - 4 - 1 =
1 - 1 =
0
---------------------------------------------------------------

b) 1 - 4/5 - 2/5 =

mmc (1, 5) = 5
5 - 4 - 2 = - 1
     5           5
---------------------------------------------------------------

c) (+ 6/5) : (- 1/2) - 3 =

6/5 * (- 2/1) - 3 =
6/5 * (- 2) - 3 =
- 12/5 - 3 =
mmc (1, 5) = 5
- 12 - 15  = - 27
      5            5
---------------------------------------------------------------
d) 3 + (- 3/4) . (- 8/9) =

3 + (24/36) =
3 - 24/36 =
mmc (1, 36) = 36
108 + 24 = 132   ou  11  ou 3  2
    36           36          3           3
---------------------------------------------------------------
e) x + 1/3 + 5/4 = 4 - 2x 

mmc (3, 4) = 12
12x + 4 + 15 = 48 - 24x
12x + 24x = 48 - 4 - 15
36x = 29
x = 29 : 36
x =  29
       36